2010
DOI: 10.1177/026142941002600103
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Preschool Teachers' Professional Ethical Behavior Perceptions, Moral Judgment Levels and Attitudes to Teaching

Abstract: Morality is the stance and attitude that makes a social human being; the display of behaviors such as praise, criticism, tolerance and intolerance, confirmation and rejection; the taking of sides by stating what one finds good or bad, right or wrong, instead of staying indifferent to what other people say and do (Pieper, 1999). Moral development needs to be taught at schools from the personality-shaping years of preschool so as to raise individuals with a strong sense of morality. Teachers are as important as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In a study by Oktay et al (2010), it is reported that morality has been an area of study in such diverse areas as religion, philosophy and psychology from Socrates to present day. It is also reported in the same study that morality has been defined in several ways.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a study by Oktay et al (2010), it is reported that morality has been an area of study in such diverse areas as religion, philosophy and psychology from Socrates to present day. It is also reported in the same study that morality has been defined in several ways.…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported in the same study that morality has been defined in several ways. According to the definition, the researchers borrowed from Oktay et al (2010), morality is a cognitive structure that includes not only conscious judgment, decision-making but also behavior about justice and injustice, right and wrong, good and bad.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations